2016
DOI: 10.1007/s40145-016-0203-3
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature hydrothermal synthesis of SrTiO3 nanoparticles without alkali and their effective photocatalytic activity

Abstract: SrTiO 3 nanoparticle (NP) photocatalyst was synthesized with a facile and environmentalfriendly hydrothermal method using tetrabutyltitanate, strontium oxide, and ethanolamine as precursors at low temperature without alkali as mineralizer for the first time. The SrTiO 3 nanoparticles were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), field emission scanning electron microscopy (FESEM), and N 2 Brunauer-Emmett-Teller (BET) method. The SrTiO 3 catalyst synthesized at 120 ℃ (ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…In 2014, Huang et al reported that raise in the temperature of synthesis has resulted in the increase of the SrTiO 3 particle size, this justified that the stronger agglomeration at higher temperature, and it was proposed that 130°C of hydrothermal temperature produced the best morphology of SrTiO 3 . In 2016, Shen et al tried to synthesise SrTiO 3 without using alkaline medium in different hydrothermal temperatures. It was reported by Shen et al, higher temperature of hydrothermal synthesis can cause nanoparticles aggregation and irregular growing particle, resulting in a heterogeneous microstructure.…”
Section: Synthesis Methods Of Srtio3mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, Huang et al reported that raise in the temperature of synthesis has resulted in the increase of the SrTiO 3 particle size, this justified that the stronger agglomeration at higher temperature, and it was proposed that 130°C of hydrothermal temperature produced the best morphology of SrTiO 3 . In 2016, Shen et al tried to synthesise SrTiO 3 without using alkaline medium in different hydrothermal temperatures. It was reported by Shen et al, higher temperature of hydrothermal synthesis can cause nanoparticles aggregation and irregular growing particle, resulting in a heterogeneous microstructure.…”
Section: Synthesis Methods Of Srtio3mentioning
confidence: 99%
“…In 2016, Shen et al tried to synthesise SrTiO 3 without using alkaline medium in different hydrothermal temperatures. It was reported by Shen et al, higher temperature of hydrothermal synthesis can cause nanoparticles aggregation and irregular growing particle, resulting in a heterogeneous microstructure. On the basis of the stability thermodynamic calculations for the hydrothermal system of Sr‐Ti, high pH and mole ratio of Sr/Ti larger than 1 were required in order to produce a high purity of SrTiO 3 nanocrystals .…”
Section: Synthesis Methods Of Srtio3mentioning
confidence: 99%
“…Moreover, there are some tiny holes with 2 nm diameter which can be ascribed to the no close packing of the SrTiO 3 . The calculated Brunauer‐Emmett‐Teller (BET) surface area is 37.41 m 2 /g which is much larger than that in the previous similar work …”
Section: Resultsmentioning
confidence: 56%
“…Such hierarchical structures often exhibit some unique features including the prevention of the agglomeration of nanosized particles, more active sites, fast ion or electrons’ transport ability, and enhanced recycle rate. The research results demonstrate hierarchical SrTiO 3 architectures characterized by the 3D assembly of hundreds of nanoparticles by the partial sharing of oriented faces, thereby displaying porous but single‐crystal‐like features . However, most of the present 3D hierarchical structures of SrTiO 3 were multistep synthesized and costly due to the use of additional surfactant to prevent from the irregular or incomplete assembly of the basic build blocks, and the specific surface area are not competitive actually …”
Section: Introductionmentioning
confidence: 97%
“…[1] Hydrogen (H 2 ) production through solar water splitting is one of the most attractive approach to transform sunlight to sustainable, renewable and green energy. Up to now, varieties of semiconductor materials such as WO 3 , [2] SnO 2 , [3] ZnO, [4] SrTiO 3 , [5] g-C 3 N 4 [6,7] and TiO 2 [8,9] with different morphologies have been widely used for the photodegradation of environmental pollutants. Among them, TiO 2 as a classical photocatalyst has been extensively researched for photocatalytic H 2 generation owning to its nontoxicity, high chemical stability, low cost, high abundance, high photocatalytic activity and suitable reduction potential for proton reduction.…”
Section: Introductionmentioning
confidence: 99%